Language Teachers and Gender Role Attitudes: Sociocultural Perspective - Permata, Kartika Indah; Azizah, Siti -; -, Nafisah -; Wati, Wiwit Rahma (Sabda: Jurnal Kajian Kebudayaan, 2024)
Schools and universities have been well-known as one of the social institutions in charge of socializing norms and values in children in terms of how they construct the concept of gender roles in society.  Sociocultural-bound attitudes of teachers play important roles in shaping or challenging the practices that highlight inequality. This study aims to investigate the influence of gender role attitudes on teacher behavior. Using the quantitative method, the data was collected by distributing questionnaires to 90 language teachers. From the F-test and T-test analysis results, it was found that there was a significant influence between variables (p≤0.05), in that, teachers’ gender role attitudes had an important impact on their teaching behavior. Then, the implication of this study is further drawn using symbolic interaction theory.